A randomized, single-center double-blinded trial on the effects of diltiazem sustained-release capsules in patients with coronary slow flow phenomenon at 6-month follow-up. - Lun Li; Ye Gu; Tao Liu; Yupeng Bai; Lingbo Hou; Zhong Cheng; Liqun Hu; Bo Gao (PLoS ONE)
Objective The aim of this study is to observe the chronic effects of diltiazem release capsules on patients with coronary slow flow (CSF) phenomenon. Methods From 2004 to 2009, 80 consecutive patients with chest pain and normal coronary arteries evidenced by coronary angiography and CSF were included in this randomized, double-blind, placebo-controlled trial. CSF patterns were evaluated by the corrected TIMI frame count. Patients were randomly assigned at 1:1 ratio to diltiazem sustained-release capsules treatment group (Dil, 90 mg twice daily) or placebo control group. Holter, liver and kidney function, treadmill exercise test, coronary angiography and left ventricular angiography were measured at baseline and after 6 months. The incidence of cardiovascular events (re-admission or progress in coronary heart disease, myocardial infarction, malignant arrhythmia or cardiac death) was evaluated during the 6 months follow up. Results Thirty-nine patients in control and 40 patients in Dil group completed the 6 months follow-up. There was no medication induced drug withdraw during follow up. Left ventricular ejection fraction was similar between the 2 groups at baseline and during follow up. Heart rate was significantly lower in Dil group than in control group and there was no symptomatic bradycardia and II and III degree atrioventricular conduction block in both groups. Significant improvement was observed in the onset of chest pain, treadmill exercise test and coronary blood flow in Dil group while these parameters remained unchanged in control group at the end of 6 months follow up. The incidence of cardiovascular events was similar between the two groups. Conclusion Diltiazem slow-release capsules improved coronary blood flow and alleviated angina in patients with CSF. Trial registration Chinese Clinical Trial Registry ChiCTR-TCC-11001864.